Augmented Reality in Vocational Education : Trend, Acquired Skills, and Future Work - Ramadhan, Muhammad Oka; Rohendi, Dedi; Handayani, Mustika Nuramalia; Abdullah, Ade Gaffar; Koehler, Thomas (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This study aims to explore the role of Augmented Reality (AR) in enhancing practical skills within vocational education, particularly in response to the evolving needs of the educational sector. Through a bibliometric analysis and comprehensive literature review, this research examines trends in AR research from 2003 to 2023. The study focuses on publication growth, citation impact, research focus, and subject area. The research method used includes bibliometric analysis and systematic literature review, with data visualized through tools like VOSviewer and Tableau. Data were collected from various academic databases, examining the distribution of publications, research impact, and citation patterns over the years. Data were analyzed using quantitative and cluster analysis to categorize research trends into six clusters: industrial architecture, biomedical surgery, product development, learning methods, AR's positive impact, and acquired skills. The study results showed that AR has a positive impact on several skill sets but may occasionally hinder others. The research also reveals that while AR applications are gaining momentum, certain areas such as Agricultural and Biological Sciences, Economics, and Nursing remain largely unexplored. This review highlights the importance of advancing AR in untouched fields and emphasizes the need for further investigation into the systematic assessment of skills acquired through AR, making this study vital for educational technology, vocational instructors, and institutions aiming to implement AR technologies effectively.